Neurocognitive predictors of length of stay within a children's psychiatric inpatient program. Issue 1 (2nd January 2020) - Kavanaugh, Brian; Studeny, Jane; Cancilliere, Mary Kathryn; Holler, Karen A.
ABSTRACT: This study investigated the neurocognitive predictors of length of stay (LOS) within a children's psychiatric inpatient program. A medical chart review was conducted for 96 children aged 6–14 years who received a neuropsychological evaluation during hospitalization. Correlation and linear regression analyses examined the influence of neurocognition (memory, construction, executive functioning [EF], and intelligence [IQ]) on subsequent LOS. Impairment/performance was calculated by the standard mean composite score and global deficit score (GDS) approaches for each domain and for overall neurocognition. Rates of impairment were similar between the two approaches (ranging from 22.9% to 45.8% across domains). Overall neurocognition (r = .347 & −.270, respectively), EF (r = .333 & −.261, respectively), and construction (r = .287 & −.240), respectively, were significantly associated with LOS utilizing the GDS and composite approaches. After controlling for clinical/demographic predictors of LOS, GDS-Total, GDS-EF/Construction, and EF/Construction composite scores significantly predicted LOS. Further, receiver operating characteristic (ROC) curve detected the GDS was able to distinguish between those children that would and would not end up having a prolonged hospitalization. The GDS and composite score approaches to neurocognitive impairment detection were similarly able to capture neurocognitive impairment and the association of impairment to LOS within a children's psychiatric inpatient program.